The Association between Organizational Market Factors and Agency Labor Utilization in U.S. Hospitals - Brad Beauvais; Rohit Pradhan; Diane Dolezel; Ramalingam Shanmugam; Dan Wood; Zo Ramamonjiarivelo (Administrative Sciences)
Objectives: To address urgent staffing shortages, hospitals increasingly rely on agency labor. Given that staffing can significantly impact hospital performance, the aim of this study was to understand the organizational and market factors associated with agency labor utilization in US hospitals. Methods: Utilizing concepts from the Resource Dependence Theory (RDT), data for the calendar year 2022 for short-term acute care in United States hospitals (n = 2756) were analyzed with logistic regression analysis. We explored total agency labor expense (operationalized as a dichotomous variable at the 75th and 90th percentiles) in the presence of numerous organizational and market independent variables. Results: The results revealed that as markets become less complex (as measured by market concentration), the level of agency labor expense increases (β: 0.843, p < 0.001), while our chosen variables related to munificence (rural location; β: −1.634, p < 0.001) and dynamism (Medicare payor mix; β: −0.025, p < 0.001) were negatively associated with an increase in total agency labor expense. Conclusions: In general, our results appear to support the tenets of the RDT. We find that increased use of agency labor in hospitals is predicated on the hospital having the financial resources and flexibility to be able to afford the higher cost of agency labor.